Nanoindentation of Nanoglasses Tested by Molecular Dynamics Simulations: Influence of Structural Relaxation and Chemical Segregation on the Mechanical Response - Adjaoud, Omar; Albe, Karsten (Frontiers in Materials, 2021)
We present molecular dynamics simulations of nanoindentation in order to investigate the ef- fects of segregation and structural relaxation on the mechanical properties of Cu 64 Zr 36 nanoglasses prepared by particle consolidation and long-time annealing. Our analysis of load-displacement curves shows that the effective elastic modulus of nano- glasses is lower than that of their homogeneous metallic glass counterpart. This is mainly because of the defective short-range order present in the glass-glass interface, but to a lesser extend due to chemical inhomogeneities. Structural relaxation obtained by long-time annealing (500ns) at 0.8 T g leads to a shift from a homogeneous deformation to a mix of homogeneous deformation and shear bands. The obtained hardness values of annealed nanoglass are comparable to those of homogenous glass samples, but significantly higher as com- pared to juvenile as-prepared nanoglass samples. The results are discussed in the context of recent nanonindentation experiments.